How Does Motivation and Dicipline Affect Employee Performance at KFC Ciplaz Parung? - Apriyana, Santa; Sunarsi, Denok; Iryadana, Mohamad Razab; Sartika, Gita (Pascasarjana Universitas Pasundan, 2024)
The purpose of this research is to determine the influence of motivation and work discipline on employee performance at Kentucky Fried Chicken (KFC) Ciplaz Parung. The method used is quantitative. The sampling technique used saturated sampling, namely 53 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that motivation has a significant effect on employee performance with a coefficient of determination value of 48.0% and the hypothesis test obtained t count > t table or (6.857 > 2.008). Work discipline has a significant effect on employee performance with a coefficient of determination value of 43.3% and hypothesis testing obtained t count > t table or (6,240 > 2,008). Motivation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 8.024 + 0.409X1 + 0.392X2. The coefficient of determination value is 58.6% while the remaining 41.4% is influenced by other factors. Hypothesis testing obtained calculated F value > F table or (35,354 > 2,790).